Analysis of the Aperture Function of the Scattering Volume of the Collimation System of the Scattering Computed Tomography of Steel Products with a Ring Detector; Russian Journal of Nondestructive Testing; Vol. 56, iss. 6 - Zhuravsky E. E. Evgeny Evgenjevich; Belkin D. S. Denis Sergeevich; Kapranov B. I. Boris Ivanovich; Chakhlov S. V. Sergey Vladimirovich (2020, 2020)
Title screen